Kepemimpinan Camat dalam Pemberdayaan Masyarakat untuk mendukung Program Pengelolaan Sampah berbasis Komunitas - Elvira Mulya Nalien (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2016)
AbstractThis research aimed to describe the six of leadership techniques of ABTB District Head according to the theory presented by Abdoelrachman in S. Pamuji and its relation to the efforts of people empowerment according to Roesmidi that is information accessibility, involvement, accountability and local organization capacity. The research method used by the writer is qualitative by using the descriptive method and inductive approach.The result of this research shows that the three of leadership techniques, which are:   a technique of followers preparation/maturation, technique of examples (teladan) and technique of persuasive have been running effectively. The human relation technique that has not been optimized caused by the district head has not fulfilled the need of properness. Ineffectiveness of communication system technique caused by the less communication and coordination between District Head and Section of Economic and People Empowerment. Meanwhile, the lack communication between District Head and the working units (SKPD) caused by there is no coordination letter for the order department manuscript. The ineffectiveness of facility supplying technique caused by the unavailability of equipment and proper working place. The internal problems in leadership technique of District Head are Habit and Superego. And external problems are people conventional mindset towards problems of garbage and there still no regulation about waste management in Bukittinggi. The efforts done by District Head is to make stronger communication and coordination with all related parties, making and directing people mindset and also conducting regulation of waste management in Bukittinggi.